Efek Antidiabetes Fraksi N-Heksana, Etil Asetat, Dan Air Dari Bunga Telang (Clitoria Ternatea L.) Pada Tikus Jantan yang Diinduksi Streptozotocin-Nikotinamid - sunarti sunarti; Peppy Octavini (Journal of Pharmaceutical and Sciences, 2023)
Diabetes mellitus is a metabolic disease characterized by increased blood glucose levels. Increased blood glucose levels are caused by impaired insulin secretion, insulin sensitivity, or both. The therapeutic target of the treatment of diabetes mellitus is controlled blood glucose levels, so that the treatment is carried out continuously and for a long time. The side effects of synthetic drugs in diabetes mellitus cause impaired kidney function, and also hypoglycemia. One alternative therapy that has fewer side effects and is safe is treatment with natural herbs. Clitoria Ternatea L. contains polar compounds such as anthocyanin flavonoids, which have antidiabetic activity. Fractionation is necessary to be able to separate compounds based on the level of polarity. This study aims to determine whether there is a hypoglycemic effect on the n-hexane, ethyl acetate, and aqueous fractions of the ethanol extract of butterfly pea flower in test animals induced by streptozotocin-nicotinamide. Wistar strain male rats were used. 30 rats were divided into 6 treatment groups consisting of normal, positive, and negative groups; the n-hexane fraction test preparation group; ethyl acetate fraction; and the water fraction group. The GOD-PAP method was used to measure blood glucose samples. The obtained blood glucose data were analyzed using the one-way ANOVA test. This study showed that the entire treatment group of the n-hexane fraction, ethyl acetate fraction, and water fraction at a dose of 400mg/KgBW had antidiabetic activity in Streptozotocin-Nicotinamide-induced test animals with an average glucose level in the n-hexane fraction of 113.89 mg/dL, the fraction ethyl acetate of 109.72 mg/dL, and the water fraction of 135.41 mg/dL. Based on the analysis of the post-hoc LSD test on day 14, the n-hexane fraction group and the ethyl acetate group at a dose of 400 mg/KgBW did not have a significant difference with the positive control. Diabetes mellitus is a metabolic disease characterized by increased blood glucose levels. Increased blood glucose levels are caused by impaired insulin secretion, insulin sensitivity, or both. The therapeutic target of the treatment of diabetes mellitus is controlled blood glucose levels, so that the treatment is carried out continuously and for a long time. The side effects of synthetic drugs in diabetes mellitus cause impaired kidney function, and also hypoglycemia. One alternative therapy that has fewer side effects and is safe is treatment with natural herbs. Clitoria Ternatea L. contains polar compounds such as anthocyanin flavonoids, which have antidiabetic activity. Fractionation is necessary to be able to separate compounds based on the level of polarity. This study aims to determine whether there is a hypoglycemic effect on the n-hexane, ethyl acetate, and aqueous fractions of the ethanol extract of butterfly pea flower in test animals induced by streptozotocin-nicotinamide. Wistar strain male rats were used. 30 rats were divided into 6 treatment groups consisting of normal, positive, and negative groups; the n-hexane fraction test preparation group; ethyl acetate fraction; and the water fraction group. The GOD-PAP method was used to measure blood glucose samples. The obtained blood glucose data were analyzed using the one-way ANOVA test. This study showed that the entire treatment group of the n-hexane fraction, ethyl acetate fraction, and water fraction at a dose of 400mg/KgBW had antidiabetic activity in Streptozotocin-Nicotinamide-induced test animals with an average glucose level in the n-hexane fraction of 113.89 mg/dL, the fraction ethyl acetate of 109.72 mg/dL, and the water fraction of 135.41 mg/dL. Based on the analysis of the post-hoc LSD test on day 14, the n-hexane fraction group and the ethyl acetate group at a dose of 400 mg/KgBW did not have a significant difference with the positive control.